Emotion Recognition on Turkish Mobile Operator Turkcell’s Call Center Calls - Tekin Altun; Hüseyin Tiryaki; Hüseyin Demirci; Yüksel Yurtay (Sakarya University Journal of Computer and Information Sciences)
A fundamental component of human intelligence is the capacity for feeling. In addition to being founded on logic and reason, human conduct is also greatly influenced by the emotions that people experience. For the purpose of this study, we classified one thousand real-life call center client voice data in the Turkish language based on the way they expressed their emotions using text emotion detection. We made use of Ekman's emotional labeling and techniques from the field of artificial intelligence, such as deep learning and other similar methods.